2016
DOI: 10.1016/j.otsr.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Does the type of sagittal spinal shape influence the clinical results of lumbar disc arthroplasty?

Abstract: This study underscores the influence of the type of sagittal curvature on the clinical results of LTDR, with type 4 patients showing inferior clinical results because of a higher rate of residual lower back pain. The indication in LTDR should be reconsidered for discogenic lower back pain in type 4 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[ 19 ] Recent research highlights a relationship between these different spine types and clinical outcomes following lumbar disc arthroplasty, suggesting that variation in the inflection point between spinal curves could be an important consideration in indicating patients for surgery. [ 20 ] Although classification systems exist in the literature to describe the sagittal profiles of patients with different types of CD, these frameworks do not incorporate assessments of the cervicothoracic inflection point. [ 21 ] The results of this study show significant variations in sagittal alignment across inflection point groups, suggesting a potential rationale for modifying existing CD classification systems to incorporate inflection point.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Recent research highlights a relationship between these different spine types and clinical outcomes following lumbar disc arthroplasty, suggesting that variation in the inflection point between spinal curves could be an important consideration in indicating patients for surgery. [ 20 ] Although classification systems exist in the literature to describe the sagittal profiles of patients with different types of CD, these frameworks do not incorporate assessments of the cervicothoracic inflection point. [ 21 ] The results of this study show significant variations in sagittal alignment across inflection point groups, suggesting a potential rationale for modifying existing CD classification systems to incorporate inflection point.…”
Section: Discussionmentioning
confidence: 99%
“…Arunakul et al [310] found no association between radiological features such as pelvic incidence and sacral slope, and clinical outcomes measured by back pain (VAS) and function (ODI) after TDR. In contrast, Laouissat et al [311] reported inferior results after TDR in patients with sagittal curvature of Roussouly type 4 [312].…”
Section: Exposure Variablesmentioning
confidence: 92%
“…As a result, the Roussouly classification has become one of the most widely used classification systems since 2005, when it was first reported. Many studies have proven the effects of the classification system on surgical decisions and outcomes [9,10,11] . In addition, studies have assessed the correlation between the morbidity of spine disorders and different Roussouly types.…”
Section: The Roussouly Classification Is Based On Features Of Spine Mmentioning
confidence: 99%